Talentism in Contemporary China: A Case Study of Labor Management in the Greater Bay Area - Strukova, Polina (Journal of Economic Sociology, 2024)
Highly qualified personnel are the most important resource for modem economic development. This paper offers an interpretation of the term “talentism” in the context of the state’s attitude towards talented specialists in the People’s Republic of China (PRC). Using examples of personnel policy in the cities of the Greater Bay Area of South China, the article examines areas and examples of working with outstanding personnel, namely mechanisms for attracting and retaining talented employees in the region. It studies the practical implementation of personnel management theory with Chinese characteristics. An analysis of scientific literature, government plans, and reports from 2004 to 2024 has enabled the systematization of accumulated experiences regarding labor force support measures, particularly in the context of integration processes occurring in the region. In particular, the following directions of talentism, which foster positive trends in working with talents in the Greater Bay Area, have been identified: development and implementation of local programs based on three- to five-year financing plans; creation of platforms for cooperation among personnel from the three administrative parts of the area, promoting active educational integration; increased mobility; expansion of social support measures for talents and their family members, including tax relief and optimization of financial incentive programs; internationalization of personnel, evaluation of specialists’ quality and their participation in project assessments, standardization, and mutual recognition of qualifications; creation of a favorable environment for further socio-economic development, along with systematic legalization of these processes. The results obtained also indicate negative aspects in working with talents in the Greater Bay Area. These include insufficient coordination between local structures in implementing abstract goals, an overly formal approach, insufficient specification of tasks, and a focus on short-term benefits without integrating talents into teamwork for the long term. Considering China’s experience will aid in organizing work with outstanding personnel in Russia to realize their potential in various regions.